Analysis Of The Contribution Of Conventional Reaction Training Management To The Dribbling Speed Of Soccer Athletes - Abdul Quddus; Lalu Hulfian (Journal Management of Sport, 2025)
Soccer is a sport that requires mastery of various basic skills, one of which is dribbling. Fast and accurate dribbling skills are crucial, especially when under pressure or during counter-attacks. Observations indicate that PS Sakra players have weaknesses in dribbling, particularly in speed and precision when handling the ball against opponents. To address this issue, this study aims to determine the effect of conventional reaction training on improving the dribbling speed of PS Sakra players. The research method used is experimental with a "one-group pretest-posttest" design. The population consisted of all 15 players from PS Sakra, who were included as samples. The results showed a significant improvement in dribbling ability after the conventional reaction training. The t-test results indicated a significant value of 0.000 < 0.05, suggesting a positive and significant effect of this training on enhancing dribbling speed.